Skilled basketball players rotate their shoulders more during running while dribbling - Fujii, K.; Yamada, Y.; Oda, S. (Perceptual and Motor Skills, 2010)
The relationship between running velocity and trunk rotation during normal running and running while dribbling was investigated in 7 male competitive basketball players and 7 male nonplayers. Participants performed a normal 20-m sprint and a 20-m sprint while dribbling a basketball. For the motion analysis, all individuals also performed normal running and running while dribbling at target of their maximal speed of sprinting and dribbling, respectively. Basketball players showed significantly smaller decreases in their running velocity from 85% maximal (target) sprint to 85% maximal (target) dribbling speeds than nonplayers. Furthermore, basketball players rotated their shoulders significantly more during target dribbling than during target running. For all participants, significant positive correlations were found between the decreases in running velocity and shoulder rotation. The results suggested that the basketball players` greater shoulder rotation during dribbling permits their running velocity to decrease less during target dribbling compared to a maximal sprint.